The investor and the securities act - Cherrington, Homer V. (New York : Da Capo Press, 1973)
It provides knowledge of the investor and the securities act.
Original ed. issued in series: Studies in economics.
Includes bibliographical references: p. 247-251.
rua 10/03/17
Loans
Keywords: Securities; Corporation law; New Deal, 1933-1939.